(untitled) (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
This article examines the role of Unmanned Aerial Vehicles (UAVs) in 21st-century border conflicts and hybrid warfare, highlighting their tactical and strategic advantages, as well as the emerging threats they pose to national security. Furthermore, it analyzes how the evolution of drone technology is reshaping contemporary border defense systems.